DAW-Based Beatmaking Creative Process: Literature Review with Guilford Indicators - Uci Rahmawati; Agus Budiman; Tati Narawati (Universitas Pendidikan Mandalika, 2026)
This study aims to map rhythmic creativity in Digital Audio Workstation (DAW)–based beatmaking using Guilford’s indicators of creativity—fluency, flexibility, originality, and elaboration—as the primary analytical framework. In higher education in music arts, these indicators are employed as an analytical lens to examine how rhythmic ideas are generated, varied, refined, and expanded during the DAW-based beatmaking process. The study adopted a directed literature review method with thematic synthesis, analyzing 40 open-access sources published between 2017 and 2025 and retrieved through database searches (e.g., DOAJ and Google Scholar) and manual reference list screening. All included sources were peer-reviewed and assigned Digital Object Identifiers (DOIs). The literature was organized into thematic clusters, including DAW pedagogy, beatmaking practices, divergent thinking and musical creativity, digital collaboration, and critiques of technology and artificial intelligence in music production. Rhythmic elements—such as patterns, grooves, accents, subdivisions, swing, microtiming, transitions, arrangement, and energy automation—were subsequently mapped onto the four creativity indicators. The findings indicate that DAWs strongly facilitate rapid idea prototyping and iterative refinement, making fluency and elaboration the most prominent creativity indicators. In contrast, flexibility and originality appear to be more contingent on task design, learners’ willingness to shift compositional strategies, negotiation with genre conventions, and the broader collaborative and technological ecosystem, including templates, presets, and AI-assisted tools. This study provides a conceptual mapping framework and illustrative assessment directions to assist lecturers in interpreting DAW project artifacts as evidence of rhythmic creative processes. In the context of music arts higher education, the proposed mapping offers a reference for designing DAW-based composition tasks and developing more consistent and transparent assessment criteria for rhythmic creativity across the four Guilford indicators. Future research is recommended to empirically test this framework through the analysis of student-produced DAW artifacts.